2009
DOI: 10.1007/s11427-009-0098-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and significance of specific and non-specific cellular immunity in patients with chronic hepatitis B caused by infection with genotypes B or C of hepatitis B virus

Abstract: The present study was designed to investigate possible relationships between the genotypes of hepatitis B virus (HBV) and the HBV-specific cytotoxic T lymphocyte (CTL) responses. HBV genotypes, HBV specific CTL HBV DNA and other markers of HBV infection were determined in 138 patients with chronic hepatitis B. The results showed that the patients infected with genotype C (n=62) had a significantly lower HBV-specific CTL response than those who were infected with HBV genotype B (P<0.01). HBV DNA titer was highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…After the initial non-specific immunity response to the HBV virus, specific immunity plays a critical role in fighting against the surviving virus18. T lymphocytes are important effector cells in specific immune response and following stimulation of HBV antigens, T cells are classified as killer T cells [mainly CD8+ cytotoxic T lymphocytes (CTLs)] and helper T lymphocytes (Th).…”
Section: Discussionmentioning
confidence: 99%
“…After the initial non-specific immunity response to the HBV virus, specific immunity plays a critical role in fighting against the surviving virus18. T lymphocytes are important effector cells in specific immune response and following stimulation of HBV antigens, T cells are classified as killer T cells [mainly CD8+ cytotoxic T lymphocytes (CTLs)] and helper T lymphocytes (Th).…”
Section: Discussionmentioning
confidence: 99%
“…In the process of clearing the virus by specific T cells, the noncytolytic route may play a more important role (11). Nonspecific cellular immunity is relatively weak in clearing HBV, but it may cause liver cell injuries in the process (12)(13)(14). Thus, we studied the changes in HBV-specific and nonspecific cellular immune responses before and after CHB progressed to chronic severe hepatitis B to provide evidence for the rational treatment, control, and prevention of deterioration of CHB.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the T cell immune response induced during HBV infection of both genotypes is consistent. Considering the most common HBV genotype infected in Chinese patients are C or B and infected with genotype C HBV will lead to more severe liver damages [ 43 ], we used the C genotype HBV plasmid to mimick HBV re-exposure, while the transgenic mice were integrated with genotype D HBV. Also, we compared the amino acid sequence between the small HBsAg of genotype C strain and D strain used in this study (data not shown) and found that most CD8 + T cell epitopes and “a” determinant region were highly conserved between these two strains.…”
Section: Discussionmentioning
confidence: 99%